Imagine being a nice guy: A note on hypothetical vs. incentivized social preferences - Christoph Bühren; Thorben C. Kundt (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
We conducted an experimental study on social preferences using dictator games similar to Fehr et al. (2008). We show that social preferences differ between participants who receive low-stakes monetary rewards for their decisions and participants who consider hypothetical stakes. The results are robust when we control for socio-demographic characteristics and par-ticipants' risk attitudes. Besides incentives, gender plays an important role for the categoriza-tion of different social preferences.
Keywords: D91; 330; social preferences; incentive mechanisms; dictator games